2020
DOI: 10.1016/j.bbrep.2020.100832
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin E and I target the JAK/STAT pathway and induce apoptosis in Sézary cells

Abstract: Cutaneous T-cell lymphomas and leukemias (CTCLs) are a heterogeneous group of extranodal non-Hodgkin's lymphomas. These are characterized by an accumulation of malignant CD4 + T-lymphocytes in the skin, lymph nodes, and peripheral blood. Novel treatment options are needed for patients who progress to advanced stage disease. Cucurbitacin I has previously shown promising results in Sézary syndrome (Sz). A plethora of cucurbitacins, however, have not yet been tested in CTCL. Herein, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…35,36 In recent studies, cucurbitacin E (3) was reported to have an inhibition effect on the phosphorylation process of STAT3. 29,37 Therefore, it would be intriguing to investigate the binding affinity of cucurbitacin E (3), relating to similar cucurbitacins 7−9 and other extracted compounds 1, 2, and 4−6 from A. crassna pericarp with the SH2 domain of STAT3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…35,36 In recent studies, cucurbitacin E (3) was reported to have an inhibition effect on the phosphorylation process of STAT3. 29,37 Therefore, it would be intriguing to investigate the binding affinity of cucurbitacin E (3), relating to similar cucurbitacins 7−9 and other extracted compounds 1, 2, and 4−6 from A. crassna pericarp with the SH2 domain of STAT3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, modulation of activation-induced cell death regulators was not observed after HECA-452 treatment of CTCL cells (data not shown). In contrast, anti-CLA antibody induced apoptotic pathways in CLAþ CTCL cells through an in vitro rapid activation (within 30 minutes) of caspases 3/7, 8, and 9 effectors compared with that of other potential or current therapeutic agents such as curbitacin, bexarotene, or cobomarsen (Brouwer et al, 2020;Seto et al, 2018). How HECA-452 exerts its effects did not require complement fixation because it induces cell death in the absence of serum (data not shown) and needs to be clarified.…”
Section: Discussionmentioning
confidence: 96%
“…Thus it is reasonable that glutamine showed a protective role against apoptosis in fish gill in the present study. In order to further illustrate the regulatory mechanism of glutamine on apoptosis, the genes expression involved in the JAK-STAT signaling pathway were evaluated, which has been identified as one of the principal pathway responsible for apoptosis in mammals [ 92 ]. JAKs including JAK1, JAK2, JAK3, and TYK2, which function as the membrane receptors, can be activated upon preferential ligand binding and then recruits and phosphorylates STATs, preferentially STAT3 and STAT5, on their tyrosine residues [ 93 ].…”
Section: Discussionmentioning
confidence: 99%